Legal Analysis of Artificial Intelligence Utilization in The Formation of Authentic Deeds Under Indonesian Notarial Law - Widya Wahyu Utami; Ratih Agustin Wulandari (CV. Norma Global, 2025)
Advancements in artificial intelligence (AI) had introduced new forms of automation into legal services, including notarial practice. This research examined the extent to which AI could be utilized in the formation of authentic deeds without violating the formal requirements stipulated under Indonesian law. Using a normative legal research methodology supported by a statute and conceptual approach, this study analyzed the Civil Code, the Notary Office Law, and the Electronic Information and Transactions Law, alongside recent scholarly literature. The findings showed that AI had no legal standing as a public official, could not verify the legal capacity or free will of the parties, and could not fulfill mandatory procedural requirements such as physical presence, reading of the deed, and witnessing. AI was therefore limited to administrative and analytical support, including drafting templates, conducting legal research, and managing electronic documents. The study concluded that the use of AI in creating authentic deeds remained legally impermissible, as the validity of such deeds depended on human supervision and direct involvement of a notary as mandated by statutory provisions.